Imaging of the Painful Hip Arthroplasty. Issue 4 (November 2016) - Hargunani, Rikin; Madani, Hardi; Khoo, Michael; Fotiadou, Anastasia; Pressney, Ian; Calleja, Michele; O'Donnell, Paul
The incidence of complications following total hip arthroplasty is low, but due to the frequency of the procedure, they are quite commonly encountered and require appropriate investigation. Complications include aseptic loosening, infection, foreign body granulomatosis (osteolysis), adverse reactions to metal debris, periprosthetic fracture, heterotopic ossification, hardware failure, and a range of soft tissue complications, all of which may result in pain. Relevant imaging findings are illustrated and the role of various imaging modalities is reviewed. A suggested approach for the radiological investigation of each potential complication is outlined, based on our experience at a specialist referral unit.